Chromium Dose Dependent Kidney Changes Morphological, Histological and Morphometrical Parameters - Kadhim, Sajjad Jubair; AL-Habib, May Fadhil Majid (American Journal of Biomedicine and Pharmacy, 2026)
Background: Chromium is a common toxic heavy metal used in many industries and has been shown to have toxic effects in many organs; the kidneys have a nephrotoxic effect, largely due to oxidative effects and cell damage. Aims: The current study aims to examine the gross anatomical, morphometric and histopathological changes in the renal tissue after exposure to chromium, in varying doses. Methods: control group and groups exposed to various doses of chromium. Gross, morphometric (length, width, weight) and histopathological changes were analysed. Result: gross changes were observed in treated groups such as; lighter kidney colour with mottling and thinning cortex. There was no significant Morphometric alteration in kidney length, kidney width was increased, and kidney weight was decreased in a dose dependent manner. Histopathologically exposed groups revealed expansion of the urinary space, glomerulus and tuft size and degeneration in the proximal convoluted tubule. Conclusion: In conclusion chromium induces significant dose-dependent renal damage at both structural and cellular levels. The findings highlight the nephrotoxic potential of chromium.